Innovation Production of Pottery According to The Sufficiency Economy Model Integrated by Banmuangnoi Chaiyaphum Community Participation - Pingthong, Narudom; Prompongsaton, Nattapong; Ampracha, Sansanee; Meemoo, Prasertsak (Journal of Fine and Applied Arts Khon Kaen University, 2022)
This research for 1. Study of Banmuangnoi Chaiyaphum’s pottery history and survey about pottery production process’s problems 2. Create pottery production innovation according to the Sufficiency economy model integrated by Banmuangnoi Chaiyaphum Community for solving pottery production process’s problems. 1. Banmuangnoi Chaiyaphum is a famous for pottery produce for a long time, current production quality and famous of stove. However, the study found 4 problems that environmental problem, economic problem, social problem and cultural problem. 2. The researcher then created the process of designing pottery innovations according to the Philosophy of sufficiency economy community integrated by Banmuangnoi Chaiyaphum community participation, integration in to the team, technology with local knowledge. The people involved in the perception, opinion, practice evaluation comment and responsibility. Phayalae kiln innovation is downdraft kiln with ceramics fiber, steel structure and Lpg can add 350 stoves at 750 degrees Celsius can reduce production time 50 percent. The results of the efficiency in aspect of showed that were not crack and still in perfect. The results of the efficiency in aspect of outcome was found that the manufacturers did not find problems to kiln operating and firing. The results of ability to solve problem are Environment : LPG reduce air pollution, Economic : Produce as much 2x. , Society and Culture : have a better relationship , takes pride in more local.